Does Multiparity Affect Periodontitis Associated Adverse Pregnancy Outcomes' Awareness? - Bashayer Bahamdain; Raghad Hasanain; Renad Barayan; Nada Bugis; Ayat Fallatah; Bader Akhozai; Mohamed Abdelrasoul (Elsevier, 2021)
Aim or Purpose: Periodontal disease (PD) is a complex dysbiotic biofilm-associated inflammatory disease of the periodontium. PD has a sizeable global burden and maybe a risk factor for pre-term birth and low birthweight.Prior learning experiences establish cognitions that may continue to be influential throughout life, multigravidity may lead to learning by experience.This study aimed to identify and measure the awareness of women in the city of Jeddah, about adverse pregnancy outcomes associated with PD. Materials and Methods: A cross-sectional study was performed, based on a validated questionnaire developed by the authors (IBR approval: UB-RES-2020-0067). A convenience sample size of 966 women, aged 20-50 years, with a confidence level of 95%, and a 5% margin of error was selected. The questionnaire was divided into three main sections: demographics, knowledge and attitude. Results: The study showed a mean score of awareness of 3.80±1.26 (54.35±17.98%) while the mean score of attitudes was 1.60±0.98 (39.91±24.42%). There was no statistically significant relationship to age group, nationality, or parity, however, scores were significant to university education level.Only 8% (n=77, p=0.007) of participants knew that gingivitis during pregnancy might cause pregnancy complications, contrarily, multiparity added no significant extra learning experience to the knowledge of adverse pregnancy outcomes associated with PD, 71.6% (n=692, p=0.007). Conclusions: Learning from previous multigravidas did not influence knowledge and awareness towards adverse pregnancy outcomes associated with PD.Individual and community based oral health educational programs, specifically during maternity are regularly needed to reduce the global burden of PD and its systemic complications.